PENGARUH UKURAN PERUSAHAAN, CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), NON PERFORMING LOAN (NPL)TERHADAP PROFITABILITAS PADA BANK UMUM SWASTA NASIONAL DEVISA YANG TERDAFTAR DI INDONESIA PERIODE 2012-2016 - BATARI AYUNDA PRAJA, NASYA; HARTONO, ULIL (Jurnal Ilmu Manajemen (JIM), 2018)
Profitability is the companys ability to make a profit. Profitability in this study is proxied with return on assets (ROA). Return on assets (ROA) is the ratio used to measure the effectiveness of the company in generating profits by utilizing the assets owned. This study aims to determine what are the factors that affect the level of profitability in a company. This study uses firm size variables, CAR, LDR, and NPL on profitability. The sample of this research is 34 companies sub sector of National Private Bank (BUSN) Foreign Exchange registered in Indonesia year 2012-2016. Sample selection using purposive sampling technique. The analysis technique used is multiple regression analysis. The results of this study indicate that firm size and CAR have a positive influence on profitability, it is in accordance with existing theories. However, the LDR variable shows that the results do not have an effect because if the LDR ratio is higher, it means that credit distribution is also high. As a result, the credit risk experienced by banks is also high so that interest on loans received as bank income is not optimal and profitability is not necessarily increased. Then the NPL variable shows the results have a positive effect on profitability in Private National Bank Foreign Exchange, the results are in accordance with the existing theory. From the results of this study, is expected to provide benefits for banks to improve bank profitability by controlling several variables that can affect the level of profitability. To facilitate creditors and debtors to assess a banking performance, this study is expected to be a reference to see the variables that affect the performance of the banking so that the creditor and debtor will be easy to make decisions. While for the next researcher is expected this research can add references and add some other variables that can affect bank proitability. Keywords: Profitability (ROA), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Ratio (NPL).